Pengaruh Kualitas Layanan dan Kepercayaan Terhadap Kepuasan Konsumen dalam Membeli Produk Online di Desa Randusari RW 07 Kelurahan Randusari Kecamatan Gadingrejo Kota Pasuruan - Nikmatul Hizah; Sugeng Pradikto (Student Research Journal, 2025)
This research aims to analyze the influence of service quality and trust on consumer satisfaction in purchasing online products in Randusari Village RW 07, Randusari Village, Gadingrejo District, Pasuruan City. Service quality includes speed, accuracy and friendliness in providing services, while trust includes aspects of transaction security, integrity and reputation of the service provider. The research method uses a quantitative approach with a survey of 99 participants in this research selected using the probability sampling method. The data collected was then analyzed by applying multiple regression techniques to determine the extent to which each independent variable (service quality and level of trust) influences the dependent variable (customer satisfaction). The research results show that these two variables, both service quality and trust, have a significant impact individually and simultaneously on the level of customer satisfaction. These findings indicate that online business actors who are able to improve service quality and strengthen consumer trust can increase overall customer satisfaction. This research provides practical contributions for online service providers in the area to improve services and build trust, as well as becoming an academic reference for further research in similar areas.